Mesorectal Excision With or Without Lateral Lymph Node Dissection for Clinical Stage II/III Lower Rectal Cancer (JCOG0212): A Multicenter, Randomized Controlled, Noninferiority Trial. Issue 2 (August 2017) - Fujita, Shin; Mizusawa, Junki; Kanemitsu, Yukihide; Ito, Masaaki; Kinugasa, Yusuke; Komori, Koji; Ohue, Masayuki; Ota, Mitsuyoshi; Akazai, Yoshihiro; Shiozawa, Manabu; Yamaguchi, Takashi; Bandou, Hiroyuki; et al.
Abstract : Objective: The aim of the study was to confirm the noninferiority of mesorectal excision (ME) alone to ME with lateral lymph node dissection (LLND) in terms of efficacy. Background: Lateral pelvic lymph node metastasis is occasionally found in clinical stage II or III lower rectal cancer, and ME with LLND is the standard procedure in Japan. ME alone, however, is the international standard surgical procedure for rectal cancer. Methods: Eligibility criteria included histologically proven rectal cancer at clinical stage II/III; main lesion located in the rectum, with the lower margin below the peritoneal reflection; no lateral pelvic lymph node enlargement; Peformance Status of 0 or 1; and age 20 to 75 years. Patients were intraoperatively allocated to undergo ME with LLND or ME alone in a randomized manner. The primary endpoint was relapse-free survival, with a noninferiority margin for the hazard ratio of 1.34. Secondary endpoints included overall survival and local-recurrence-free survival. Analysis was by intention to treat. Results: In total, 701 patients were randomized to the ME with LLND (n = 351) and ME alone (n = 350) groups. The 5-year relapse-free survival in the ME with LLND and ME alone groups were 73.4% and 73.3%, respectively (hazard ratio: 1.07, 90.9% confidence interval 0.84–1.36), with a 1-sided P value for noninferiority of 0.0547. The 5-year overall survival, and 5-year local-recurrence-free survival in the ME with LLND and ME alone groups were 92.6% and 90.2%, and 87.7% and 82.4%, respectively. The numbers of patients with local recurrence were 26 (7.4%) and 44 (12.6%) in the ME with LLND and ME alone groups, respectively ( P = 0.024). Conclusions: The noninferiority of ME alone to ME with LLND was not confirmed in the intent-to-treat analysis. ME with LLND had a lower local recurrence, especially in the lateral pelvis, compared to ME alone.